Pengaruh NIM dan CAR terhadap ROA pada Bank BUMN yang terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Martina Dama Yanti; Noviansyah (Jurnal Manajemen Bisnis Unbara, 2025)
This study aims to determine the influence of NIM and CAR on ROA in state-owned banks listed on the Indonesia Stock Exchange during the 2019–2023 period. The population of this study consists of the financial statements of state-owned banks listed on the IDX. The analytical method used is panel data regression, with the assistance of EViews 13 software. The results indicate that NIM and CAR simultaneously have a significant influence on ROA. However, partially, NIM does not have a significant effect on ROA, and similarly, CAR has a significantly affect ROA. The coefficient of determination (R-squared) is 0.554145 or 55.41%, which means that NIM and CAR explain 55.41% of the variation in ROA, while the remaining 44.59% is influenced by other factors not included in the model such as NPL, LDR, DER, BOPO and other financial rations.